Social Change and Artistic Change on Autonomy of the Artistic Sphere Structure Influence in Sociology of Arts - Rius-Ulldemolins, Joaquim (Política y Sociedad, 2020)
The interpretation of the influence of social change on artistic change has been a controversial issue since the beginning of sociology. In spite of the challenging status of the arts to sociological theory their contributions have been important to develop a social sociological perspective of art change. However, its heteronomous interpretation of the artistic with respect to the social, especially by the post-Marxist or neodurkhemian perspective, imposes severe limits on the analysis of artistic change, which will only be overcome from the Weberian conceptualization of art as an autonomous social sphere. From this base, three currents of the sociology of art are analysed (structuralist, interactionist and institutionalist) which attempt to decrypt the black box that represents the social influence in the artistic creation in a more meso-sociological way of interpretation. However, the emergence of the postmodern orientations represents a provocative but confusing return of macro level that puts into question the art’s autonomy and heteronomy debate and, in this case, the determination of the structure in the interpretation of artistic change. The critical analysis of the contribution of each current and perspective of the sociology of art on the autonomy and influence of the structure will be the object of this article.